2018
DOI: 10.1029/2017wr021769
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pore‐Scale Model of Drainage in Granular Porous Media: The Pore‐Unit Assembly Method

Abstract: Dynamics of drainage is analyzed for packings of spheres, using numerical experiments. For this purpose, a dynamic pore‐scale model was developed to simulate water flow during drainage. The pore space inside a packing of spheres was extracted using regular triangulation, resulting in an assembly of grain‐based tetrahedra. Then, pore units were constructed by identifying and merging tetrahedra that belong to the same pore, resulting in an assembly of pore units. Each pore unit was approximated by a volume‐equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
5
0
2
Order By: Relevance
“…The pore-network extraction algorithm (Thompson et al, 2008) defined pore bodies similarly to the common definition of largest inscribed sphere in a pore space region (Scheidegger, 1958) but, additionally, employed a burn algorithm to associate pore voxels outside of each inscribed sphere to a pore body. The result is that the pores generated by this extraction algorithm are similar to pore units (e.g., Sweijen et al, 2016;Sweijen et al, 2017;Sweijen et al, 2018) as each identified pore body encompasses the entire pore volume between a set of grains as opposed to the pore volume encompassed by the largest 10.1029/2019WR025381 inscribed sphere. Throats are also defined in a similar manner to pore units as the facet area between two pore bodies and contain no volume.…”
Section: Imaging Reconstruction and Segmentationmentioning
confidence: 99%
“…The pore-network extraction algorithm (Thompson et al, 2008) defined pore bodies similarly to the common definition of largest inscribed sphere in a pore space region (Scheidegger, 1958) but, additionally, employed a burn algorithm to associate pore voxels outside of each inscribed sphere to a pore body. The result is that the pores generated by this extraction algorithm are similar to pore units (e.g., Sweijen et al, 2016;Sweijen et al, 2017;Sweijen et al, 2018) as each identified pore body encompasses the entire pore volume between a set of grains as opposed to the pore volume encompassed by the largest 10.1029/2019WR025381 inscribed sphere. Throats are also defined in a similar manner to pore units as the facet area between two pore bodies and contain no volume.…”
Section: Imaging Reconstruction and Segmentationmentioning
confidence: 99%
“…Alternatively, with the rapid development of computational software, several numerical and analytical methods have been proposed to simulate the multiphase flow in porous media. Among these methods, the lattice Boltzmann method (LBM), a pore-scale numerical method based on the kinetic Boltzmann equation, has shown immense potential for investigating the microscale mechanism of the multiphase flow phenomenon. Eshraghi et al reported that the LBM model could be used in the simulation of dendritic solidification with 36 billion grid points, and the parallel efficiency was almost 100% using 1000–4068 CPU cores. Li et al reported that the three-dimensional (3D) multiphase LBM simulation cases (model size: 512 × 256 × 256) could achieve a parallel efficiency of approximately 60% with 400K CPU cores using a hybrid, heterogeneous, multiple data programming model.…”
Section: Introductionmentioning
confidence: 99%
“…Joekar-Niasar and Hassanizadeh [150] studied dynamic capillary flow in angular pore network using DPNM and gave the same conclusion as Karadimitriou, Hassanizadeh, Joekar-Niasar and Kleingeld [51] that proposed constitutive surface (P c -S w -A nw ) exists for non-equilibrium drainage and imbibition but the difference between dynamic surface and static surface increases with both viscous forces and capillary number increase. Later, Sweijen, et al [219] upgraded the angular DPNM to the tetrahedra DPNM using the Discrete Element Method (DEM). Then, they carried out the DPNM simulation through the genuine tetrahedra pore unit formed by an assembly of granular particles.…”
mentioning
confidence: 99%
“…Then, they carried out the DPNM simulation through the genuine tetrahedra pore unit formed by an assembly of granular particles. The same as Joekar-Niasar and Hassanizadeh [150], Sweijen, Hassanizadeh, Chareyre and Zhuang [219] also applied the static capillarity into pore-scale modelling and more focused on generating macroscale dynamic effects by regional heterogeneity. Finally, they concluded that regional heterogeneity-induced fingering flow formed dynamic capillarity effects in macroscale.…”
mentioning
confidence: 99%